Driving Mechanisms of an Extreme Winter Sea Ice Breakup Event in the Beaufort Sea - Jonathan W. Rheinlænder; Richard Davy; Einar Ólason; Pierre Rampal; Clemens Spensberger; Timothy D. Williams; Anton Korosov; Thomas Spengler (Geophysical Research Letters)
Abstract The thick multiyear sea ice that once covered large parts of the Arctic is increasingly being replaced by thinner and weaker first‐year ice, making it more vulnerable to breakup by winds. We use the neXtSIM sea ice model to investigate the driving mechanisms behind a large breakup event in the Beaufort Sea during winter 2013. Our simulations are the first to successfully reproduce the timing, location, and propagation of sea ice leads associated with wind‐driven breakup and highlight the importance of accuracy of the atmospheric forcing, sea ice rheology, and changes in sea ice thickness. We found that the breakup resulted in enhanced export of multiyear ice from the Beaufort Sea. Overall, this leads to a relatively thinner and weaker simulated ice cover that potentially preconditions earlier breakup in spring and accelerates sea ice loss. Finally, our simulations indicate that large breakup events could become more frequent as Arctic sea ice continues to thin.